2021
DOI: 10.1101/2021.03.02.433677
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Apparent diet digestibility of captive colobines in relation to stomach types with special reference to fibre digestion

Abstract: Colobine monkeys are known for the anatomical complexity of their stomachs, making them distinct within the primate order. Amongst foregut fermenters, they appear peculiar because of the occurrence of two different stomach types, having either three (tripartite) or four (quadripartite, adding the praesaccus) chambers. The functional differences between tri and quadripartite stomachs largely remain to be explained. In this study, we aim to compare the apparent digestibility (aD) in tripartite and quadripartite … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…Our data thus imply that colobine digestive adaptations are more flexible than previously assumed. Supporting this, it has recently been suggested that colobine species with a tripartite stomach such as T. obscurus and S. vetulus are less susceptible to extreme bouts of malfermentation when fed highly digestible diets like fruits and/or seeds due to a reduced food intake capacity (Hoshino et al 2021, Matsuda et al 2019). However, in comparison to T. obscurus and S. vetulus , the stomach of many foregut fermenting colobine species are poorly understood, including in P. femoralis .…”
Section: Discussionmentioning
confidence: 97%
“…Our data thus imply that colobine digestive adaptations are more flexible than previously assumed. Supporting this, it has recently been suggested that colobine species with a tripartite stomach such as T. obscurus and S. vetulus are less susceptible to extreme bouts of malfermentation when fed highly digestible diets like fruits and/or seeds due to a reduced food intake capacity (Hoshino et al 2021, Matsuda et al 2019). However, in comparison to T. obscurus and S. vetulus , the stomach of many foregut fermenting colobine species are poorly understood, including in P. femoralis .…”
Section: Discussionmentioning
confidence: 97%
“…Assuming that digestibility is a function of digesta retention and diet quality (Hume, 2005), in both scenarios a net increase in digestible material intake or a tolerance for lower quality food would be the consequence. In feeding experiments, this should for example be reflected in higher fiber digestibility achieved by species with a quadripartite stomach (Hoshino et al, 2021). To date, these findings must be considered preliminary, as both our stomach tissue weights and the digestibility findings of Hoshino et al (2021) are based on a very limited number of a single species with a quadripartite stomach— N. larvatus .…”
Section: Discussionmentioning
confidence: 99%
“…In feeding experiments, this should for example be reflected in higher fiber digestibility achieved by species with a quadripartite stomach (Hoshino et al, 2021). To date, these findings must be considered preliminary, as both our stomach tissue weights and the digestibility findings of Hoshino et al (2021) are based on a very limited number of a single species with a quadripartite stomach— N. larvatus . Evidently, more studies including other species with quadripartite stomachs would be required to test general hypotheses about this stomach type comprehensively.…”
Section: Discussionmentioning
confidence: 99%
“…Over 3500 h of observation based on full day follows (including observations from all hours of the day) revealed previously unknown data about proboscis monkey foraging behavior (Matsuda et al, 2009a; Matsuda et al, 2009b). As a result of adaptation to a folivore diet, the proboscis monkey evolved the foregut fermentation digestive system with four (“quadripartite”) chambers in the forestomach (Hoshino et al, 2021; Matsuda et al, 2022; Matsuda, Chapman, & Clauss, 2019) along with a long digesta retention time, that is, approximately 40 h (Matsuda et al, 2015) and is the only primate that exhibits regurgitation and remastication (Matsuda et al, 2011). To elucidate the functional significance of regurgitation and remastication, we extended our research to other primate species and other mammalian taxa.…”
Section: Main Findingsmentioning
confidence: 99%